1985
DOI: 10.1136/hrt.53.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of diltiazem and propranolol, alone and in combination, in patients with stable angina pectoris.

Abstract: The antianginal effects of diltiazem 180 mg/day and propranolol 240 mg/day, alone and in combination, were investigated in 15 patients with effort related angina in a double blind placebo controlled crossover trial, with each period of treatment lasting four weeks. Patients performed a symptom limited treadmill exercise test at the end of each period of treatment. Mean (SEM) time to onset of angina was increased from 293(32) s when receiving placebo to 347(38) s when receiving diltiazem alone, to 350(30) s whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

1985
1985
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 15 publications
0
5
0
2
Order By: Relevance
“…There were 28 studies (37 comparisons) of a CCB added to a BB ( n = 2468); 7–35 12 studies (12 comparisons) of a BB added to a CCB ( n = 1489); 9,11,12,1416,19,20,24,25,29,34 7 studies (8 comparisons) of a LAN added to a BB or CCB ( n = 329); 7,3640 3 studies (4 comparisons) of ranolazine added to a BB or CCB ( n = 1388); 41–43 8 studies (9 comparisons) of trimetazidine added to a BB or CCB ( n = 2875); 4451 1 study of ivabradine added to a BB ( n = 889). 52 No studies were found that evaluated the impact of nicorandil in an add-in role on either ETT or clinical measures of anti-anginal efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…There were 28 studies (37 comparisons) of a CCB added to a BB ( n = 2468); 7–35 12 studies (12 comparisons) of a BB added to a CCB ( n = 1489); 9,11,12,1416,19,20,24,25,29,34 7 studies (8 comparisons) of a LAN added to a BB or CCB ( n = 329); 7,3640 3 studies (4 comparisons) of ranolazine added to a BB or CCB ( n = 1388); 41–43 8 studies (9 comparisons) of trimetazidine added to a BB or CCB ( n = 2875); 4451 1 study of ivabradine added to a BB ( n = 889). 52 No studies were found that evaluated the impact of nicorandil in an add-in role on either ETT or clinical measures of anti-anginal efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…Kenny et al [61] have clearly demonstrated that diltiazem, a different calcium antagonist, although still active at the L channel, when used in combination with propranolol was superior to either drug alone in prolonging the mean time to onset of angina in the 15 patients studied. Strauss and Parisi showed that a combination ofpropranolol and diltiazem significantly improved exercise duration in 24 patients with chronic, stable effort angina, when compared to propranolol or propranolol and placebo [62].…”
Section: Chronic Stable Anginamentioning
confidence: 96%
“…The equilibria between the monoprotonated (BH + ) and non-protonated (B) antianginals (acid-base constants, pK a = 7.7-9.45, see Table 1) take place outside the working pH range of a C18 column (3)(4)(5)(6)(7). For these compounds, the retention was thus the same using mobile phases of SDS at pH 3 and 7.…”
Section: Elution Behaviour In Sds-pentanol Mobile Phasesmentioning
confidence: 99%
“…If treatment of angina with calcium channel blockers or ␤-blockers alone in monotherapy fails, an association of both can be effective and safe even in the paediatric age [2][3][4][5][6][7][8][9][10][11]. ␤-Blockers diminish the heart rate, resulting in decreased myocardial oxygen demand and increased oxygen delivery to the heart, and also decrease myocardial contractility, thus helping to conserve energy or decrease demand.…”
Section: Introductionmentioning
confidence: 99%